1999
DOI: 10.1021/ja9910107
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Proteins by Design. Cross-Linked Bis-Hemoglobin

Abstract: A new type of multifunctional reagent creates a specific connection within and between two hemoglobin tetramers, resulting in a cross-linked bis-tetramer (“CLBT”). The tetrafunctional reagent (N,N‘-5,5‘-bis[bis(3,5-dibromosalicyl)isophthalyl]terephthalamide, DBIT) was prepared by conversion of the corresponding tetraacid to the tetrakis(3,5-dibromosalicylate). Deoxy hemoglobin reacts with DBIT to give a cross-linked bis-tetramer as the major product. Patterns in tryptic digests reveal that there are modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 34 publications
3
45
0
Order By: Relevance
“…Reagent 1, with a central sulfone, gave the highest yield of a ∼128 kDa material (Table 1). Globin chain analysis (32) through C4 reverse-phase HPLC showed that only one component derived from native hemoglobin had been modified (Figure 2 (20) and counterparts isophthalyl phosphastes (23,24) that produced cross-linked hemoglobin bis-tetramers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reagent 1, with a central sulfone, gave the highest yield of a ∼128 kDa material (Table 1). Globin chain analysis (32) through C4 reverse-phase HPLC showed that only one component derived from native hemoglobin had been modified (Figure 2 (20) and counterparts isophthalyl phosphastes (23,24) that produced cross-linked hemoglobin bis-tetramers.…”
Section: Resultsmentioning
confidence: 99%
“…Since partial hydrolysis will lead to a more complex mixture of products, we chose to use dibromosalicylates to minimize partial destruction of the reactive portion of the reagents. The synthesis of acyl dibromosalicylate derivatives, which was achieved by reacting activated carboxylic acids with protected dibromosalicylic acid, gave useful yields of reagents (20). Although the acyl dibromosalicylates are less reactive than acyl phosphates and have additional steric limitations in their reactivity patterns, they efficiently cross-linked hemoglobins as bis-tetramers (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining the reagent with hemoglobin gave material that had a molecular weight of about 128 kDa (by size exclusion chromatography based on standards from hemoglobin oligomers) (40). Polyacrylamide gel electrophoresis under nondenaturing conditions also gives the major peak at the same retention time as a 128 kDa standard.…”
Section: Synthesizing Bis-tetramersmentioning
confidence: 99%